Characterization of chemokine and cytokine expression pattern in tuberculous lymphadenitis patient - Novita, Bernadette Dian; Tjahjono, Yudy; Wijaya, Sumi; Theodora, Imelda; Erwin, Ferdinand; Halim, Stefan Wilson; Hendrawan, Bobby; Jaya, David Karunia; Tahalele, Paul L. (Frontiers in Immunology, 2022)
Introduction: C-C chemokine receptor-2 (CCR-2) and C-C chemokines ligand-5 (CCL-5) play an important role in the migration of monocytes, macrophages, dendritic cells, and activated T cells against Mycobacterium tuberculosis (M.tb). Meanwhile, STAT-3 and SOCS-3, activated by IL-6 and IL-10 in tuberculosis infection, play an important role in phagocytosis, inflammation, and granulomatous forming processes that may lead to tuberculosis treatment success or failure. However, there is no data about the expression of those markers in tuberculous lymphadenitis. The characterization of those markers is very critical to put a fundamental basis to understand the homing mechanism of tuberculous lymphadenitis. Aim of study: the specific objective of this study is to characterize the expression pattern of CCR-2-CCL-5, IL-6, IL-10, STAT-3, and SOCS-3 in tuberculous lymphadenitis. Methods: The study was performed on 27 cases of tuberculous lymphadenitis node biopsies. Diagnosis of tuberculous lymphadenitis was based on the clinical criteria and the presence of histological features characteristic of tuberculosis granulomas. Afterwards, immunohistochemistry was stained with CCR-2, CCL-5, IL-6, IL-10, STAT-3, and SOCS-3. A semi-quantitative analysis of IHC images was performed to examine protein expression in stained preparations. The expression was also manually counted. Results: Compared with the normal area, both lymphocytes and macrophages expressed strongly CCR-2-, CCL-5, IL-6, while IL-10, STAT-3- and SOCS-3- expressed low. There was strong positive correlation between CCR-2 with IL-6 (p = 0,83) and IL-10 (p = 0,83). Conclusion: The chronic infection process of tuberculous lymphadenitis was characterized by the expression of IL-10low, STAT-3low, SOCS-3low, CCR-2high, CCL-5high, and IL-6high.